2017
DOI: 10.17554/j.issn.2409-5680.2017.03.64
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Amplitude of Accommodation in Different Room Illumination while Using VDU as a Target

Abstract: illumination. Further, to associate AA among genders, age groups, race and refractive error for different levels of room illumination was not significant (p > 0.05). However, amplitude of accommodation between 15-21years and 22-28 years showed significant (p = 0.047) difference for the first room illumination. CONCLUSION:The illumination has no clinically significant effect on amplitude of accommodation. INTRODUCTIONSince 1972, research into the effects of the VDU on the eye expanded [1] . Due to technologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…This study showed no significant difference in AA among ethnicities (Chinese, Malay, and Indian) when using the push-up ( p = 0.539), pull-away ( p = 0.558), minus lens ( p = 0.622), and modified push up ( p = 0.950) methods and dynamic retinoscopy ( p = 0.566). This finding agrees with Majumder [13] that there was no significant difference ( p > 0.05) between the AA according to ethnicity in all three-room illuminations of 24, 17, and 4 lux. In another Malaysian-based study, Majumder and Ying [9] showed a significant difference ( p < 0.05) between the AA at 20-degree downgaze in Chinese and non-Chinese participants.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study showed no significant difference in AA among ethnicities (Chinese, Malay, and Indian) when using the push-up ( p = 0.539), pull-away ( p = 0.558), minus lens ( p = 0.622), and modified push up ( p = 0.950) methods and dynamic retinoscopy ( p = 0.566). This finding agrees with Majumder [13] that there was no significant difference ( p > 0.05) between the AA according to ethnicity in all three-room illuminations of 24, 17, and 4 lux. In another Malaysian-based study, Majumder and Ying [9] showed a significant difference ( p < 0.05) between the AA at 20-degree downgaze in Chinese and non-Chinese participants.…”
Section: Discussionsupporting
confidence: 92%
“…However, no significant difference was found for the minus lens ( p = 0.051) or modified push-up ( p = 0.216) technique. Majumder [13] reported no significant difference ( p > 0.05) in AA according to sex for any of the room illuminations ( p = 0.529, p = 0.459, and p = 0.302 for 23, 17, and 4 lux, respectively). In addition, Majumder and Ying [9] showed no significant difference in AA according to sex for all directions of gazes (p = 0.18, p = 0.18, p = 0.68, and p = 0.80) for primary gaze, 20 degrees up gaze, 20 degree downgaze, and 40 degrees downgaze, respectively.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations